2017
DOI: 10.1111/his.13250
|View full text |Cite
|
Sign up to set email alerts
|

Alterted SLIT2/ROBO1 signalling is linked to impaired placentation of missed and threatened miscarriage in early pregnancy

Abstract: SLIT2/ROBO1 signalling may regulate trophoblast differentiation and invasion causing restricting β-hCG production, shallow trophoblast invasion and inhibiting placental angiogenesis in missed and threatened miscarriage during the first trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…We detected association signals for SNPs in a region that encompassed SLIT2 and for SNPs in a region downstream of ROBO1 , which encodes the receptor for SLIT2. SLIT2 and ROBO1 encode proteins of the SLT2-ROBO1 signaling pathway; previous studies have indicated that this pathway is associated with different types of pregnancy complications, including preeclampsia [27,28], impaired placentation of missed and threatened miscarriage in early pregnancy [29], trophoblast invasion, and vascular remodeling during ectopic tubal pregnancy [29,30]. Our hypothesis-free GWAS study provides evidence that these genes have a role in another pregnancy complication, SPTB.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…We detected association signals for SNPs in a region that encompassed SLIT2 and for SNPs in a region downstream of ROBO1 , which encodes the receptor for SLIT2. SLIT2 and ROBO1 encode proteins of the SLT2-ROBO1 signaling pathway; previous studies have indicated that this pathway is associated with different types of pregnancy complications, including preeclampsia [27,28], impaired placentation of missed and threatened miscarriage in early pregnancy [29], trophoblast invasion, and vascular remodeling during ectopic tubal pregnancy [29,30]. Our hypothesis-free GWAS study provides evidence that these genes have a role in another pregnancy complication, SPTB.…”
Section: Discussionmentioning
confidence: 60%
“…In addition to their functions in biogenesis of the placenta and maintenance of pregnancy, trophoblasts may participate in labor induction [43]. Two‐thirds of early pregnancy failures may present with reduced trophoblast invasion [29]. SLIT-ROBO signaling may play autocrine and/or paracrine roles in trophoblast functions, such as differentiation and invasion, by influencing the migration of trophoblastic cells [29,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often known as essential in implantation are numerous regulatory proteins recognized to play a key role in cancer cell invasion [29] .E-cad is found in humans in trophoblasts, and homophilic interaction between cytotrophoblast and endometrium are thought to be mediated through it. This may mean that E-cad involves in the embryo implantation initial stage [30] , and it is down-regulated in placental villi during early pregnancy in patients with spontaneous miscarriage may be regarded as one of risk factors of this condition [31] .However, no evidence exists to indicate whether or not the down-regulation of E-cad expression in villi or the up-regulation of E-cad expression in extravillous trophoblasts marks the beginning or the terminal stages of trophoblast differentiation in patients with missed and threatened miscarriage [32] . In our study, we evaluated the serum level of MycBP and E-cad and explored the correlation between these two biomarkers with this clinical condition.…”
Section: Introductionmentioning
confidence: 99%
“…3 The most common factors contributing to the EM include cytogenetic defects of the conceptus, anatomical abnormalities, autoimmune disorders, infections, and endocrine and psychological factors. 4,5 Recent studies suggest that poor placentation and conceptus loss may result from key defects such as fetus abnormalities, primary trophoblast dysfunction, abnormal karyotype, 6 defective placental angiogenesis, 7 genetic aberration, elevated inflammatory cytokines level, 8,9 imbalance between trophoblastic apoptosis, 10 macroautophagy and hypoxic milieu. 11 The etiology of EM remains complex, and in approximately 50% of the cases, causes and molecular mechanisms continue to remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%